The Legal Smuggling Through Nominee Agreement & Its Implications for Coastal Beach Management - Ulya Atsani; Roni Efendi; Dodi Syahputra (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research aims to explore and analyze the impacts caused by legal smuggling through nominee agreements in the management of coastal areas in the Mentawai Islands Regency. As an agreement that is not permitted in Indonesian contract law, nominees certainly have implications, especially in terms of investment practices and land ownership in the Mentawai Islands Regency. Then the Constitution and the Basic Agrarian Law have regulated very strictly regarding land rights and ownership. Historical experience has led Indonesia to establish regulations on land rights and their management in Indonesia. However, the legal facts that occur are that not a few foreign citizens own land in Indonesia, such as in the Mentawai Islands Regency by smuggling the law, including through nominee agreements. The writing method uses an empirical legal research type and is oriented toward primary data sources obtained through interviews and document studies. The survey results show that out of 85 resorts registered with the Tourism, Youth and Sports Office, there are 11 resorts owned by foreign citizens by smuggling the law through nominee agreements which imply being null and void because they are not by the Civil Code. Furthermore, impunity for this legal smuggling means that residents will lose their identity as a customary law community because the land as their local cultural identity has been taken over by foreign countries.